Comparison of attitudes towards digital piracy between downloaders and non-downloaders - Liang, Johan; Phau, Ian (Korean Scholars of Marketing Science, 2012)
This study investigates the difference perspectives between downloaders and nondownloaders towards digital piracy by using multiple regression analysis. A number of implications for businesses will be discussed, suggestions for future research are reviewed and the main contributions of the study will also be delineated.